The Influence Of Building And Atmosphere On The Development Of Coffee Shop Businesses In The SDGs Era Through Social Media As Intervening Variable - Faqih, Achmad; Aisyah, Siti; Wachdijono, Wachdijono; Rosdiana, Eva (Jurnal Manajemen Industri dan Logistik, 2022)
The purpose of this research is to analyze the variables of the coffee shop building and atmosphere directly on the social media variables, and to analyze the influence of the coffee shop building and atmosphere variables indirectly on the business development variables through social media variables. The research time is in May-July 2021 and the location is a coffee shop in Cirebon City. The research design is quantitative with a survey method. The research population is the owner of the coffee shop, amounting to 85 people so that the sampling technique is carried out by census. Measurement of data with Liker Scale and data analysis using path analysis. The results of the study concluded that the variables of the building and the atmosphere of the coffee shop had a positive effect on social media, and the building and atmosphere of the coffee shop had a positive effect on business development through social media in the coffee shop in the city of Cirebon. The results of this study are expected to be input for coffee shop owners in managing their business in this SDGs era.